Analysis of performance in different agility tests in young soccer players - Perri, E.; Massari, M.; Trecroci, A.; Iaia, F. M.; Alberti, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Agility, described as the ability to perform quick runs with directional changes, is an important component of soccer performance (Sheppard J.M. et al. 2006). Agility is a complex capacity (Young W.B. at al. 2002) and further information are needed to better elucidae its reproducibility and the different skills affecting performance during sprint/ agility tests. Therefore, the aim of the present study was to: i) determine the reliability of three different sprint/agility tests; ii) examine any existing relationships among the tests and iii) analyse their physical characteristics. Methods: Ten young soccer players from the same professional team (16.9±0.3 years; 178.7±4.8 cm; 68.8±5.6 kg) were involved in the study. The participants carried out two testing sessions separated by one week. Each testing day included three trials of following three tests: 1) 20-m straight sprint 2) Sprint with 90° turns and 3) Sprint with 90° turns dribbling with the ball (Sporis G. et al. 2010). Performance was measured using photoelectric cells (Optojump, Microgate, BZ, Italy), and GPS (Qstarz 15 Hr, Italy). Only the best trial was considered and the following parameters analysed: time, maximal speed (MS), mean power (MP), mean power in change of direction (CODMP). Results: A significant difference in performance time between Sprint and Agility with ball in test-retest was 3.2±0.1 vs 3.1±0.1s (p<0.01), 9.1±0.4 vs 8.9±0.5 (p<0.01), respectively. The coefficients of variation between the test-retest were: 1.8 ± 1.3, 2.8 ± 1.9% and 2.3 ± 1.0% for Sprint Agility and Agility with ball, respectively. No correlation in performance time were observe between 20-m Sprint and Agility (r=0.11 p>0.05), Sprint and Agility with ball (r=0.33 p>0.05) as well as Agility and Agility with ball (r=0.16 p>0.05). No differences (p>0.05) were noted in CODMP between Agility and Agility with ball25.9±1.7 vs 24.2±2.0 W*kg-1 (p>0.05). Significant differences (F=966.5 p<0.001) in MP were shown between 20 m sprint vs agility (p<0.001), 20-m sprint vs agility with ball (p<0.001) and agility vs agility with ball (p<0.001). Discussion: A variation was observed in performance time between the test-retest indicating high sensitivity and the need of a familiarization period when performing sprint/ agility tests. The pronounced differences in MP together with the absence of relationships found among the three different tests suggest that different abilities upregulate performance during sprint, agility and agility with ball.